Design of Thrift Shop E-Catalog Information System Using PHP and Javascript (Case Study: Meytwins Thrifting) - Christina Meylianti; Muhamad Femy Mulya; Pramitha Dwi Larasati; Saipul Anwar (Fakultas Teknik Universitas Bhayangkara, 2023)
Currently, there is a popular trend among the younger generation regarding the use of used clothes. What's interesting is the emergence of the online thrift shop, which is a type of business that is booming in the fashion sector by selling used clothes through online platforms. Generally, these business people get clothing supplies in the form of bales (sacks) imported from abroad. The Online Thrift Shop has received a positive response from many young people by offering clothing that has a unique style in a retro or vintage atmosphere from the 90s, as well as world-famous brands. However, one of the obstacles faced by the online thrift shop is the mismatch between the products received by consumers and what was initially displayed by the seller. There are situations where the goods delivered to consumers do not match the description given by the seller. This phenomenon is one of the shortcomings that need to be considered in online thrift shop operations. There are many online shops that sell goods to consumers that do not match what is offered. This makes consumers' shopping confidence and comfort less comfortable. The aim of the research is to build an information system in the form of an e-catalog that can simplify the buyer process without having to come to the store, as well as provide information related to fashion products that are suitable for consumers or customers. In this research, we used the prototype method, then for the system design tools, we used UML modeling, and for database modeling, we used ERD. Information system built using PHP and Javascript. Then, based on the test results using BlackBox Testing from several respondents, the success rate of the system built was 95%. Keywords: E-Catalog, Prototype, PHP, Javascript, Blackbox Testing